PRISM: A Novel Visual Instrument to Facilitate Self-Reflection and Learning Progress in Undergraduate Dental Education. (16th August 2022) - Schmalz, Gerhard; Sensky, Tom; Kullmann, Henrike; Büchi, Stefan; Ziebolz, Dirk
Abstract : Objectives . PRISM (Pictorial Representation of Illness and Self-Measure) is a simple visual tool that has been successfully used as a visual metaphor in medicine. In this pilot study, PRISM was used for the first time to test its potential to support self-reflection and expectations of learning in dental students. Methods . Dental student volunteers (25 3 rd year, 10 4 th year, and 10 5 th year) participated. Using both quantitative and qualitative methods, PRISM interviews were compared with a numerical scale in assessing learning objectives concerning theoretical knowledge, practical skills, interest, and training need in the field of conservative dentistry. Results . Overall, 71% of total student group stated that they would draw personal consequences for their studies due to participating in the PRISM interviews. Compared to the numeric scales, PRISM was rated as more helpful regarding appraisal of students' theoretical knowledge (p = 0.02 ), practical skills (p < 0.01 ), training needs (p < 0.01 ), importance of dental subspecialties (p < 0.01 ), and facilitating self-reflection (p = 0.02 ). In focus groups, students commented that PRISM fostered the development of a trusting relationship with their teacher. Strengths of PRISM mentioned by the students included being able to observe and manipulate a visual summary of their individual learning needs and seeing their different learning needs in relation to one another. Conclusion . In this pilot study, dental students evaluated PRISM to be superior against numeric scales. Furthermore, it ameliorated the communication with teachers. The PRISM task is both simple and brief and warrants further exploration as a useful tool for self-reflection in dental education.